Louisiana - Hintz, Martin (New York : Children's Press, 1998)
Describes the history, geography, ecology, people, economy, cities, and sights of the Pelican State of Louisiana.
Includes bibliographical references and index.
10 - 12 years
Keywords: Louisiana -- Juvenile literature